2016
DOI: 10.2166/ws.2016.086
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection effect of pressurized carbon dioxide on Escherichia coli and Enterococcus sp. in seawater

Abstract: Ship ballast water should be disinfected before being discharged into the ocean to avoid the dispersal of non-native species into the marine environment. This study presents the results of using pressurized carbon dioxide (CO2) at less than 1.0 MPa for inactivating Escherichia coli and Enterococcus sp. in artificial seawater (3.4% salinity). The bactericidal effects of pressurized CO2 were assessed using a liquid-film-forming apparatus under various conditions of pressure, temperature, and working volume ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The disinfection efficiency of pressurized CO 2 substantially increased with increasing temperatures (11-28°C) at 0.7 MPa (Figure 7). The E. coli load was reduced by more than 5.0 log within 25 min of treatment at 11°C, whereas only 20, 12, and 10 min of pressurized CO 2 treatment at 15, 18, and 20-28°C, respectively, were required to reduce the E. coli load to a similar extent [23]. Taken together, these findings suggest that E. coli inactivation by pressurized CO 2 could be efficiently conducted at low-pressure (0.7 MPa) and ambient temperature Figure 6.…”
Section: Effects Of Pressure and Temperaturementioning
confidence: 92%
See 4 more Smart Citations
“…The disinfection efficiency of pressurized CO 2 substantially increased with increasing temperatures (11-28°C) at 0.7 MPa (Figure 7). The E. coli load was reduced by more than 5.0 log within 25 min of treatment at 11°C, whereas only 20, 12, and 10 min of pressurized CO 2 treatment at 15, 18, and 20-28°C, respectively, were required to reduce the E. coli load to a similar extent [23]. Taken together, these findings suggest that E. coli inactivation by pressurized CO 2 could be efficiently conducted at low-pressure (0.7 MPa) and ambient temperature Figure 6.…”
Section: Effects Of Pressure and Temperaturementioning
confidence: 92%
“…However, the increased pressure application from 0.7 to 0.9 MPa did not result in significant increase in the rate of bacterial inactivation. These data indicated that the optimal CO 2 pressure for inactivating E. coli was in the range of 0.7-0.9 MPa, and hence, 0.7 MPa was chosen as the optimal pressure condition for effective bactericidal activity [23].…”
Section: Effects Of Pressure and Temperaturementioning
confidence: 99%
See 3 more Smart Citations